P282 Outcome for PsA biologic switchers following primary inefficacy of TNFi therapy in a secondary care cohort: sequential TNFi versus switching mode of action. (20th April 2020) - Naja, Meena; Santos, Liliana R; Shipa, Muhammad; Mandy, Greenwood; Castelino, Madhura
Abstract: Background: TNFi are the most used first line of biologic disease modifying anti-rheumatic drugs (bDMARDs) in PsA. In primary loss of response (PLR) to TNFi, there is no current evidence that directs the choice of second line bDMARDs. Our aim in this work was to compare drug survival for those who switched to a second TNFi versus alternative agents in real life. Methods: Data was analysed retrospectively from a cohort of 400 PsA patients followed through from 2002-2019. Statistical analysis was carried out with descriptive statistics and t-test analysis using SPSS version 22. Results: Out of 400 patients, 220 (55.0%) were started on bDMARD treatment. Of these 220, 212 (96.5%) were started on TNFi as initial therapy. PLR was seen in 42 of these patients (19.8%). The median drug survival of initial TNFi therapy was 7.1 months (interquartile range [IQR] 3.6 - 53.4 months). Of the 42 patients with PLR: 32 (76.2%) were switched to a second TNFi; 6 (14.3%) were switched to ustekinumab and 4 (9.5%) were switched to secukinumab. 21 of the 32 patients switched to a second TNFi were subsequently switched onto a third biologic due to treatment failure (65.6%). The median drug survival of the second TNFi in this group was 7.7 months (IQR 3.0 - 26.3 months). 3 out of the 6 (50%) patients who were switched to ustekinumab were then subsequently switched, this was due to primary inefficacy in 66.7% and adverse events in 33.3%. The median drug survival of ustekinumab in this group was 10.0 months (IQR 0.0 - 16.0 months). All 4 patients switched to secukinumab continue on this treatment with no drop outs, giving a median drug survival 12.3 months (IQR 6.5 - 19.5 months). Conclusion: Our data suggests that patients with PLR to TNFi in PsA who switched mode of action to IL-17 inhibitor appeared to have better drug survival than subsequent TNFi or IL-12/23 inhibitors. Exploring the clinical biomarkers for those with successful switch to non-TNFi bDMARD in a larger cohort would help with targeting the most appropriate individuals and early disease control. Disclosures: M. Naja None. L. R. Santos None. M. Shipa None. G. Mandy None. M. Castelino None.